2017
DOI: 10.1124/jpet.117.240788
|View full text |Cite
|
Sign up to set email alerts
|

Brain Disposition of cis-para-Methyl-4-Methylaminorex (cis-4,4′-DMAR) and Its Potential Metabolites after Acute and Chronic Treatment in Rats: Correlation with Central Behavioral Effects

Abstract: para-Methyl-4-methylaminorex (4,49-DMAR) is a phenethylamine derivative with psychostimulant activity whose abuse has been associated with several deaths and a wide range of adverse effects. We recently validated a high-performance liquid chromatography-tandem mass spectrometry method to measure the compound's concentrations in plasma, and we applied it to describe the pharmacokinetic properties of 4,49-DMAR after a single dose in rats. In this study, we investigated the brain disposition and metabolism of cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…It was also hypothesized that the methyl group might inhibit the hydrolysis of the amino-oxazoline ring. Lucchetti and colleagues could produce similar results for (±)- cis -4,4'-DMAR215. They discovered four metabolites, caused by hydrolysis, hydroxylation, deamination (which has already been shown for 4-MAR) and oxidation of the compound.…”
Section: Pharmacokineticsmentioning
confidence: 60%
See 2 more Smart Citations
“…It was also hypothesized that the methyl group might inhibit the hydrolysis of the amino-oxazoline ring. Lucchetti and colleagues could produce similar results for (±)- cis -4,4'-DMAR215. They discovered four metabolites, caused by hydrolysis, hydroxylation, deamination (which has already been shown for 4-MAR) and oxidation of the compound.…”
Section: Pharmacokineticsmentioning
confidence: 60%
“…They discovered four metabolites, caused by hydrolysis, hydroxylation, deamination (which has already been shown for 4-MAR) and oxidation of the compound. The main metabolite located in plasma and brain was the one not detected in 4-MAR, caused by oxidation of 4,4'-DMAR’s para -methyl group215. It has been demonstrated that aminorex is mostly eliminated renally over the course of 72 hours211.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, 4,4′-DMAR was associated with 31 deaths in Europe. For this reason, the Commission on Narcotic Drugs, in 2016, decided to internationally control this new synthetic drug by adding it into Schedule II of the Convention on Psychotropic Substances of 1971 [12,13]. 4,4′-DMAR was initially sold as a "research chemical" on the illicit Internet market in powder form, under different names (e.g., "4-methylU4Euh", "4-methyl-euphoria", "Serotoni") [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…So far, little is known about the pharmacokinetics of 4,4′-DMAR and its analogs; Lucchetti et al [12] identified four metabolites (hydroxylated, carboxylated, deaminated, and 4-methylnorephedrine) of cis-4,4′-DMAR in rat plasma and brain tissues. No information was, instead, available on the urinary excretion profile of the 4,4′-DMAR isomers.…”
Section: Introductionmentioning
confidence: 99%